Obesity Severity, Dietary Behaviors, and Lifestyle Risks Vary by Race/Ethnicity and Age in a Northern California Cohort of Children with Obesity. (14th January 2016) - Ford, Margaret C.; Gordon, Nancy P.; Howell, Amanda; Green, Cheryl E.; Greenspan, Louise C.; Chandra, Malini; Mellor, R. Grant; Lo, Joan C.
Abstract : Identification of modifiable behaviors is important for pediatric weight management and obesity prevention programs. This study examined obesogenic behaviors in children with obesity in a Northern California obesity intervention program using data from a parent/teen-completed intake questionnaire covering dietary and lifestyle behaviors (frequency of breakfast, family meals, unhealthy snacking and beverages, fruit/vegetable intake, sleep, screen time, and exercise). Among 7956 children with BMI ≥ 95th percentile, 45.5% were females and 14.2% were 3–5, 44.2% were 6–11, and 41.6% were 12–17 years old. One-quarter (24.9%) were non-Hispanic white, 11.3% were black, 43.5% were Hispanic, and 12.0% were Asian/Pacific Islander. Severe obesity was prevalent (37.4%), especially among blacks, Hispanics, and older children, and was associated with less frequent breakfast and exercise and excess screen time, and in young children it was associated with consumption of sweetened beverages or juice. Unhealthy dietary behaviors, screen time, limited exercise, and sleep were more prevalent in older children and in selected black, Hispanic, and Asian subgroups, where consumption of sweetened beverages or juice was especially high. Overall, obesity severity and obesogenic behaviors increased with age and varied by gender and race/ethnicity. We identified several key prevalent modifiable behaviors that can be targeted by healthcare professionals to reduce obesity when counseling children with obesity and their parents.